National Socioeconomic Surveys in Forestry : Guidance and Survey Models for Measuring the Multiple Roles of Forests in Household Welfare and Livelihoods - Bakkegaard, Riyong Kim; Agrawal, Arun; Animon, Illias; Hogarth, Nicholas; Miller, Daniel; Persha, Lauren; Rametsteiner, Ewald; Wunder, Sven; Zezza, Alberto (Rome: FAO, 2017)
FAO along with CIFOR, IFRI (International Forestry Resources and Institutions), and the World Bank LSMS (Living Standards Measurement Study) and PROFOR programs came together with the objective of developing specialized modules on forest and wild products (herein referred to as forestry modules) to fill current information gaps concerning the relationship of forest and wild products to household well-being. This sourcebook builds on the results from field tests to present a set of survey modules on forest and wild products that can be used to provide information on the socioeconomic contributions of forests and non-forest environments to household welfare and livelihoods.